Construction Hybrid immunoglobulin All Four Dengue serotype Using Mesenchymal Stem - A’la, Rofiqul; Ernawati, Rahaju; Retno L, Nunuk Dyah; Mufasirin, Mufasirin; Ma’ruf, Anwar; Rantam, Fedik A. (KnE Life Sciences, 2017)
The dengue virus is a member of vector-borne diseases that causes zoonotic disease and spreads rapidly in the world. No single treatment or vaccine yet is available that is recommended and there is no correlation with protectiveness against this disease. The heavy chain (VH) and light chain (VL) variables are molecules of immunoglobulin G (IgG) is the smallest part of the antibody. Although the part-time domain variable is short, it can be used as a long-term and rapid immune booster in the immune system. In this study we tried to clone an encoding gene that was able to influence the adaptive immune response to dengue 1-4 by using MSC as a gene carrier. The target scFv-IgG gene has been successfully integrated into the plasmid. Plasmids that we have linearly transfected into the MSC. From the cDNA synthesis results continued with PCR synthesis with primer FGHV and RGHA obtained bands in accordance with the target of 404 bp. The scFv gene encoding IgG can be integrated with MSC Keywords: immunetherapy; dengue; hybrid; scFv-IgG; mesenchymal